Pengaruh massage counterpressure terhadap intensitas nyeri persalinan kala I fase aktif - Suyani Suyani; Mochammad Anwar; Herlin Fitriana Kurniawati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
The research is a quasi-experiment with nonequivalent control group design with objective to investigate the effect of counterpressuremassageon the pain intensity of active phase fisrt stage labor. The total population of the research were all of labor mother at Yogyakarta City Primary Health Centre which were taken using purposive sampling technique with 31 sales. The data were analyzed using T-test. According to the research result, the average of the intensity score before and after the treatment to the control group shows zero difference (p= 0,147). The difference comparison of pain intensity in the control and treatment group is significantly different withmean difference 2,097 (p0,001;95%CI 1665-2,529). This shows that counterpressuremassage is able to reduce the pain intensity compared to the standard treatment. The multivariate test shows that counterpressuremassage mostly decreases pain as much as 2,356 compared to psychosocial assistance.